2019
DOI: 10.1038/s41401-018-0197-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of immune response following prolonged myocardial ischemia/reperfusion with and without cyclosporine A

Abstract: Understanding the dynamics of the immune response following late myocardial reperfusion is critical for the development of immunomodulatory therapy for myocardial infarction (MI). Cyclosporine A (CSA) possesses multiple therapeutic applications for MI, but its effects on the inflammation caused by acute MI are not clear. This study aimed to determine the dynamics of the immune response following myocardial ischemia/reperfusion (I/R) and the effects of CSA in a mouse model of prolonged myocardial ischemia desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 50 publications
3
36
0
Order By: Relevance
“…Scrutiny of the relative timings of cytokine elevation after ischaemic injury in relation to neutrophil mobilisation does not support their role in this early mobilisation, since both the onset and peaks in neutrophil mobilisation occur prior to those for cytokine elevation (17, 18, 43) . IL-8 injection mobilised neutrophils from the bone marrow (13) , but after reperfusion in AMI, even in blood from the coronary sinus (undiluted myocardial effluent), the elevation is modest (0.1-fold) (18, 19) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Scrutiny of the relative timings of cytokine elevation after ischaemic injury in relation to neutrophil mobilisation does not support their role in this early mobilisation, since both the onset and peaks in neutrophil mobilisation occur prior to those for cytokine elevation (17, 18, 43) . IL-8 injection mobilised neutrophils from the bone marrow (13) , but after reperfusion in AMI, even in blood from the coronary sinus (undiluted myocardial effluent), the elevation is modest (0.1-fold) (18, 19) .…”
Section: Discussionmentioning
confidence: 97%
“…The bone marrow has been regarded as the principal source for neutrophils that are mobilised to peripheral blood after injury, because (i) it is the primary site for granulopoiesis (8-10) ; (ii) it contains ample reserves of mature cells and; (iii) releases neutrophils in response to injection of exogenous chemokines (12-16) . However, the divergent timings of neutrophil mobilisation (rapid) (1, 20) and chemokine elevation (delayed) in vivo (17, 18, 43) suggest that additional processes may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of MI with permanent coronary ligation, we showed that activated CD8 + T cells expressing CD69 and CD107a markers were recruited within the ischemic myocardium. Such CD8 + T cell in ltration in the heart has also been observed in experimental transient ischemia 27 . In humans, CD8 + T cells were identi ed in the ischemic heart tissue at early stage after MI, but predominated in the periinfarct region one week after MI.…”
Section: Discussionmentioning
confidence: 58%
“…However, both pathophysiological conditions cause extensive tissue injury associated with the inflammatory response at ischemic and non-ischemic areas after MI. Indeed, neutrophils and inflammatory cytokines significantly increased in the heart at 1 day after permanent occlusion of LCA and myocardial I/R [47][48][49] . In the previous reports, suppression of the inflammatory response including infiltrating neutrophils decreased myocardial infarct size and improved cardiac function in permanent occlusion of LCA 50,51 and myocardial I/R 52,53 .…”
Section: Discussionmentioning
confidence: 99%